Barriers and facilitators to integrating depression care in tuberculosis services in South Asia: a multi-country qualitative study - Olamide Todowede; Saima Afaq; Anoshmita Adhikary; Sushama Kanan; Vidhya Shree; Hannah Maria Jennings; Mehreen Riaz Faisal; Zara Nisar; Ikram Khan; Geetha Desai; Rumana Huque; Najma Siddiqi (BMC, 2023)
Abstract Background Depression is common among people with tuberculosis (TB). The condition is typically unrecognised or untreated despite available and effective treatments in most low- and middle-income countries. TB services in these countries are relatively well established, offering a potential opportunity to deliver integrated depression screening and care. However, there is limited evidence on how such integration could be achieved. This study aimed to understand the barriers and facilitators to integrate depression care in TB services. Methods We conducted nine workshops with 76 study participants, including people with TB, their carers, and health service providers in Bangladesh, India, and Pakistan, seeking views on integrating depression care into TB clinics. We used a deductive thematic approach to analyse the translated transcripts of audio recordings, contemporaneous notes made during workshops for Bangladesh and India and workshop reports for Pakistan. Using the SURE (Supporting the Use of Research Evidence) thematic framework, we extracted and categorised barriers and facilitators into various domains. Results Reported barriers to integrating depression care in TB services included lack of knowledge about depression amongst patients and the staff, financial burden, and associated stigma for people with TB and their carers. Government buy-in and understanding of how to identify and screen for depression screening were potential facilitators reported. Additionally, breaking through mental health stigma and providing the additional resources required to deliver this service (human resources and consultation time) were essential for integrating depression and TB care. Conclusions Depression is a common condition found among people with TB, requiring early identification among people with TB. Integrating depression care into Tb services by health workers requires the availability of political support and the provision of resources.